Cловообразование имен лиц с суффиксами -(н)ик и -щик в русском языке XVII века : (на материале мемуаров Котошихина "O России в царствование Алексея Михайловича") - Kamińska, Anna (Acta Universitatis Lodziensis. Folia Linguistica, 2002)
This article is devoted to the word-formation of personal nouns with suffixes: -(n)ik and -ščik in Russian Language of 17th century. The analysis of the Kotosixin’s memoirs leads to the conclusion that both -(n)ik and -ščik were two of the most widespread suffixes in forming personal nouns according to people’s activities or their distinctive features. What is more, -(n)ik became especially productive in professional names including simple manufacturers, craftsmen and masters. Apart from that, special attention is paid to the contexts illustrating the usage of the derivatives like: горшечник, каретник and their equivalents: горшечного дела мастер, каретный мастер.